Characterization and Functional Analysis of Small Heat Shock Protein Genes (Hsp22.2 and Hsp26.7) in Sitodiplosis mosellana Diapause - Qitong Huang; Qian Ma; Xiaobin Liu; Keyan Zhu-Salzman; Weining Cheng (Insects)
Small heat shock proteins (sHsps) play crucial roles in organismal adaptation to stress tolerance. Sitodiplosis mosellana, a devastating insect wheat pest, undergoes long obligatory larval diapause to survive temperature extremes during summer and winter. To elucidate the function of sHsps in this process, two sHsp-encoding genes (SmHsp22.2 and SmHsp26.7) were characterized from S. mosellana, and their responsiveness to diapause and thermal stress, as well as their roles in cold stress, was analyzed. Both SmHsp22.2 and SmHsp26.7 possessed the canonical α-crystallin domain and lacked introns. Quantitative PCR indicated significant upregulation of SmHsp22.2 and SmHsp26.7 during diapause, especially in summer and winter. Notably, SmHsp22.2 exhibited higher expression in summer relative to winter, whereas SmHsp26.7 showed the opposite profile. Moreover, short-term heat shock (≥35 °C) in over-summering larvae or cold shock (≤−10 °C) in over-wintering larvae was found to trigger transcriptional upregulation of both genes, while prolonged temperature extremes (i.e., 45–50 °C or −15 °C) did not elicit a comparable response. RNA interference-mediated knockdown of both genes significantly increased the mortality of S. mosellana larvae under cold stress. These findings indicate the importance of both SmHsps in diapause and environmental adaptation in S. mosellana.